2007
DOI: 10.1111/j.1525-1438.2007.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of intra- and postoperative complications related to debulking surgery with bowel resection in patients with FIGO stage III–IV ovarian cancer

Abstract: The surgical treatment of advanced ovarian cancer is based on the maximal debulking with widening the operation range to the infiltrated organs. The aims are as follows: (1) the assessment of the quantity and quality of intra- and postoperative complications in patients with advanced ovarian cancer in which partial bowel resection was performed and (2) the evaluation of intra- and postoperative complications related to surgery with bowel resection and anastomosis, compared to Hartmann's procedure. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The difference in the survival of patients in the two groups did not achieve statistical significance (20). However, the observation that survival in the two groups was similar, following an analysis of the two types of surgical treatment in advanced ovarian cancer patients without lymphadenectomy, is significant.…”
Section: Intraoperative Complicationsmentioning
confidence: 80%
See 1 more Smart Citation
“…The difference in the survival of patients in the two groups did not achieve statistical significance (20). However, the observation that survival in the two groups was similar, following an analysis of the two types of surgical treatment in advanced ovarian cancer patients without lymphadenectomy, is significant.…”
Section: Intraoperative Complicationsmentioning
confidence: 80%
“…In their study, Bidzinski et al (20) reported surgery-related complications in the two types of surgical treatment, in advanced ovarian cancer patients (FIGO III-IV). The difference in the survival of patients in the two groups did not achieve statistical significance (20).…”
Section: Intraoperative Complicationsmentioning
confidence: 99%
“…However, in the last mentioned paper, a high rate of colostomies brings attention. In 2007, we reported our initial experience in performing rectosigmoid resection or colectomy in patients with FIGO stage III and IV ovarian cancer [ 9 ]. Our series from 2007 consisted of 39 patients treated in a single center.…”
Section: Discussionmentioning
confidence: 99%
“…A few series of extended surgical procedures including abdominal and diaphragmatic peritonectomy, partial liver resection, and partial pancreatectomy or splenectomy have been published. The resections of parts of the digestive tract, especially the large bowel, are increasingly commonly performed [ 7 9 ]. According to the authors of those reports, the risk associated with such procedures seems justified in view of an improved prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that radical pelvic resection (i.e., radical oophorectomy, en bloc rectosigmoid colectomy, or modified posterior pelvic exenteration) is feasible and effective to completely remove pan-pelvic disease without significant morbidity [22,23] . Extensive bowel resections are also performed as part of cytoreductive procedures [24][25][26] . Salani et al reported that multiple (≥2) bowel resections were necessary in order to obtain an optimal or complete RD in ASOC [27] .…”
Section: Reasons Conditionsmentioning
confidence: 99%